Quantitation of Plasma Levels of Tetranectin - Effects of Oral Contraceptives, Pregnancy, Treatment with L-Asparaginase and Liver Cirrhosis - Kluft, C; Los, P; Clemmensen, I; Brommer, E J P; Gevers Leuven, J A; Boks, A L; Vellenga, E (Thrombosis and Haemostasis, 1989)
Tetranectin is a tetrameric protein that binds to kringle 4 of plasminogen. Increase of electrophoretic mobility of the otherwise slowly migrating tetranectin in the presence of ethylenediaminetetraacetate was used to develop a reproducible electroimmunoassay to quantify plasma levels. Plasma levels in normals were found within narrow limits of 100 ± 16 (SD)%, (100% =0.15 pmol/1). There was no difference between males and females, smokers and non-smokers, and there were no significant changes with age from 20 to 49 years.Patients with severe liver cirrhosis showed a large variation in plasma tetranectin levels but no systematic or average reduction, in contrast to strong reductions in plasma levels of other proteins. Patients treated with L-asparaginase showed a gradual reduction in time in plasma levels of various proteins, though tetranectin showed no significant reduction.It is concluded that tetranectin can be assayed reproducibly in plasma and has a well regulated plasma level. This level is not sensitive to conditions with reductions in synthesis of many proteins, such as during cirrhosis of the liver and during L-asparaginase therapy. The reductions in plasma levels during the use of oral contraceptives and pregnancy indicate involvement of sex steroids in the metabolism of tetranectin.
Keywords: Fibrinolysis; Plasminogen; Tetranectin; Kringle 4; L-asparaginase; Liver disease; Oral contraceptives; Pregnancy